2020
DOI: 10.1016/j.celrep.2020.107838
|View full text |Cite
|
Sign up to set email alerts
|

Atrx Deletion in Neurons Leads to Sexually Dimorphic Dysregulation of miR-137 and Spatial Learning and Memory Deficits

Abstract: Highlights d Loss of ATRX in neurons has sexually dimorphic effects on long-term spatial memory d Targeted deletion of neuronal ATRX in mice causes ultrastructural synaptic defects d ATRX null neurons show sex-specific changes in miR-137 and target synaptic transcripts d ATRX directly binds and suppresses miR-137 in males via enrichment of H3K27me3

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 99 publications
1
28
0
Order By: Relevance
“…Using transmission electron microscopy, we previously reported that ATRX‐cKO mice have a significant reduction in the number of presynaptic vesicles, a wider synaptic cleft, and a larger postsynaptic density in the CA1 stratum radiatum compared to controls (Tamming et al, ). While a wider synaptic cleft is expected to result in slower onset or duration of excitatory synaptic responses, our field potential analyses were unable to detect any such changes between groups (results not shown).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using transmission electron microscopy, we previously reported that ATRX‐cKO mice have a significant reduction in the number of presynaptic vesicles, a wider synaptic cleft, and a larger postsynaptic density in the CA1 stratum radiatum compared to controls (Tamming et al, ). While a wider synaptic cleft is expected to result in slower onset or duration of excitatory synaptic responses, our field potential analyses were unable to detect any such changes between groups (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, they displayed deficits when tested a week later, suggesting long‐term spatial memory impairment in these mice. They also displayed impaired contextual fear memory, compared to controls, 24 hr after conditioning, and exhibited a drastic deficit when tested in the paired‐associate learning touchscreen task, which relies on the hippocampus (Tamming et al, ). The decrease of hippocampal apical dendritic CA1 LTP that we identified in the present study may account for the hippocampus‐dependent learning and memory impairment in ATRX‐cKO mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations